Alteration of public contracts and its interface with public procurement objectives: a comparative analysis - Barreto-Cifuentes, Carlos Sebastian (2022)
The law of alterations of public contracts was for some time a matter reserved for national contract law. Thus, countries regulated the area via private contract law or administrative law, depending on their traditions, and procurement concerns were not especially observed as important in the area. However, the “expansionary” nature of procurement has arrived at these shores and national and international objectives in public procurement are now closely regarded in the law of alterations of public contracts. This has occurred, as demonstrated in this thesis, in a reactive manner, and generally based on a case-by-case evolution that is not always orderly. This reactive and case-by-case expansion has created scattered and not necessarily orderly/systematised rules in some of the analysed regulatory frameworks. Scholarly presents similar features.